Introduction: Mental Health and the Law - Robin Fretwell Wilson (Washington University Journal of Law & Policy, 2004)
The mentally ill face some vexing problems. Fortunately, many of these are ones where a body of interdisciplinary work can assist legal decisionmakers to protect more adequately the interests of the mentally ill, and those of society. This set of five articles prepared for the March 2004 Washington University School of Law conference on Mental Health and the Law brings this literature to bear on the gamut of issues raised in society’s struggle to better address the pressing needs of the mentally ill. Given the centrality of competence determinations to this field, it is appropriate that this set contains a pair of articles about competence. The set also devotes much-needed attention to ethical dilemmas posed by the representation of clients afflicted with mental health problems—filling an important hole in the mental health literature. Giving credence to Justice Brandies’s observation that the states are laboratories of experimentation, this set of articles also reviews innovative approaches to state regulation of mental health professionals and the provision of services, and highlights the promise of these approaches. Importantly, the authors candidly point out some of the failures of state law. Obviously, we should learn from our failures as well as our successes. Perhaps most notably, these articles examine the intersection of the mental health system with legal systems, and highlight the costs of artificially parsing human problems—which for all of us are complex and messy—into neat little boxes labeled “juvenile justice” or “family and dependency” law. By unraveling the complex interplay between these systems, the authors advance considerably our understanding of the challenges facing the mentally ill in navigating them. The articles also suggest concrete ways in which legal education can instill a greater awareness of mental health issues. By doing so, the authors give hope that the next generation of attorneys, legal policymakers, and regulators will better respond to the needs of the mentally ill.
Keywords: Mental health; Criminal justice administration